Penentuan Unsur Tanah Jarang Kelompok Sedang secara Voltammetri Pindai Linier Menggunakan Elektrode Grafit Pensil - Hartati, Yeni Wahyuni; Utami, Elsa Nur; Hendrati, Diana; Sofyatin, Titin (Al-Kimia, 2016)
Rare earth elements play an important role in a variety of applications, mostly for high-tech industries. But their presence in mineral jointly separation makes it difficult to determine the content of rare earths because each element has physical and chemical properties are almost identical. The purpose of this study is the use of a linear scan voltammetry method to study the electrochemical characteristics of the medium rare earth element group (Sm, Gd, Eu, Tb), as an alternative method of separation and analysis of rare earth elements. The electrode used is a graphite pencil electrodes without modification, with a variety of supporting electrolyte. The results obtained show some supporting electrolyte provides good reduction peak for gadolinium, compared to the peaks of the reduction potential of the single rare earth ions other. The potential range of the most well using pencil graphite electrode obtained at 0.50 V to -1.00 V. Analysis of single gadolinium provide linear regression equation in a concentration range of 4.0 to 10.0 mg/L by the equation Y = 0.9862 X + 0.828 with R2 = 0.9954. The limit of detection is determined from the linear regression obtained 0.72 mg / L.